Research on Matching Optimal State Points of Air Conditioning Performance - Yu Zhen; Chen Haining; Pan Likui; Wang Fuqiang (Zhileng xuebao)
In order to match the best state point of air-conditioning performance, this paper selects an air conditioning unit with a refrigerating capacity of 5.15 kW as a research object. The influence of the charging capacity, the subcooling degree and the superheat degree at the evaporator outlet of the air conditioning system on the refrigerating capacity and energy efficiency of the system is experimentally studied. The theoretical matching curves of SH-Q, SC-EER, SC-Q, SH-EER are proposed, and the best state point of the air conditioning system is matched through the curve. The way to achieve the best state point matching can be divided into two parts: 1) the first charge amount of refrigerant should be based on the matching curve to find the most suitable evaporation superheat degree and condensation subcooling degree of the system; 2) according to the evaporation superheat degree and condensation subcooling degree, the charge amount and throttling intensity are then adjusted to match the best state point of refrigeration efficiency of the air conditioning system. According to the matching curve, the best matching state points of the system are obtained, that is, the most suitable superheat degree and subcooling degree is 1.3 ℃ and 6 ℃, respectively, and the corresponding refrigeration energy efficiency is 2.94, which is 11.4% higher than the minimum value of 2.64 during the experiment.